The Effectiveness of the Use of Number Smart Board Learning Media to Improve Early Childhood Numeracy Skills - Korlina Makulua; Franklin Stevan Dahoklory; Clinton Lumaupuy (International Journal of Language and Ubiquitous Learning, 2024)
Background. Learning in early childhood is an important foundation in the development of cognitive abilities, especially in numeracy skills. However, challenges in teaching the concept of counting effectively are often faced by educators. Interesting learning media, such as number smart boards, are expected to help overcome this obstacle. This media is designed to make it easier for children to understand the concept of numbers and basic operations of mathematics through fun and interactive methods. Purpose. This study aims to test the effectiveness of the use of number smart board learning media in improving numeracy skills in early childhood. In addition, this study also focuses on how this media affects children's motivation to learn and whether there is a significant difference between the use of this media and conventional learning methods. Method. This study uses a quantitative approach with an experimental design. The subjects of the study were children aged 4-6 years in a kindergarten who were divided into two groups, namely an experimental group that used the media of a number smart board and a control group that used traditional learning methods. Data collection was carried out through observations, numeracy tests, and questionnaires to measure children's motivation to learn. Results. The results showed that children who learned to use a number smart board experienced a significant improvement in numeracy compared to the control group. In addition, the motivation to learn in the experimental group was also seen to be higher. Conclusion. The use of number smart board learning media has been proven to be effective in improving early childhood numeracy skills. This media is also able to increase children's learning motivation, making it an effective alternative to conventional learning methods.